Tinjauan Keputusan Menteri Agama Nomor 606 Tahun 2020 terhadap Kesesuaian Hak Amil atas Dana Zakat, Infak, dan Sedekah - Farid Raihan Fadhillah; Maman Surahman (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Zakat, infaq, and alms (ZIS) are important instruments in the Islamic economic system aimed at realizing social justice and community welfare. To ensure that ZIS management complies with sharia principles and state regulations, the Indonesian government issued the Decree of the Minister of Religious Affairs (KMA) Number 606 of 2020, which regulates guidelines for zakat management, including provisions regarding amil rights. This study aims to analyze the implementation of KMA No. 606 of 2020 in the management of amil rights over ZIS funds at Baitulmaal X, examine its compliance with sharia principles and applicable regulations, and identify factors influencing its implementation. This research uses a descriptive qualitative method with a case study approach, employing data collection techniques through interviews, observations, and documentation. The results show that Baitulmaal X consistently applies the provisions of KMA No. 606/2020 while maintaining efficiency and prudence principles. The realization of amil rights from zakat funds averaged 6.1% over the last three years, which is significantly below the maximum limit of 12.5%. Furthermore, ZIS fund management is conducted transparently under the supervision of the Sharia Supervisory Board and through the application of PSAK 409. These findings emphasize the importance of professionalism and accountability in zakat fund governance to ensure compliance with sharia principles while supporting institutional sustainability. Abstrak. Zakat, infaq, dan sedekah (ZIS) merupakan instrumen penting dalam sistem ekonomi syariah yang bertujuan mewujudkan keadilan sosial dan kesejahteraan umat. Untuk memastikan pengelolaan ZIS berjalan sesuai prinsip syariah dan regulasi negara, pemerintah menerbitkan Keputusan Menteri Agama (KMA) Nomor 606 Tahun 2020 yang mengatur pedoman pengelolaan zakat, termasuk ketentuan mengenai hak amil. Penelitian ini bertujuan untuk menganalisis implementasi KMA Nomor 606 Tahun 2020 dalam pengelolaan hak amil atas dana ZIS di Baitulmaal X, mengkaji kesesuaiannya dengan prinsip syariah dan regulasi yang berlaku, serta mengidentifikasi faktor-faktor yang mempengaruhi penerapannya. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan pendekatan studi kasus melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa Baitulmaal X telah menerapkan ketentuan KMA No. 606 Tahun 2020 secara konsisten dengan tetap menjaga prinsip efisiensi dan kehati-hatian. Realisasi hak amil dari dana zakat rata-rata hanya sebesar 6,1% dalam tiga tahun terakhir, jauh di bawah batas maksimal 12,5%. Selain itu, pengelolaan dana dilakukan secara transparan dengan pengawasan Dewan Pengawas Syariah serta penerapan PSAK 409. Temuan ini menegaskan pentingnya profesionalisme dan akuntabilitas dalam tata kelola dana zakat agar sesuai dengan prinsip syariah dan mendukung keberlanjutan lembaga.